2017
DOI: 10.1002/alr.22014
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional image analysis for staging chronic rhinosinusitis

Abstract: Background Traditional methods of staging chronic rhinosinusitis (CRS) through imaging do not differentiate between degrees of partial mucosal sinus inflammation, thus limiting their utility as imaging biomarkers. We hypothesized that software-aided, quantitative measurement of sinus inflammation would generate a metric of disease burden that would correlate with clinical parameters in patients with suspected sinus disease. Methods Adults with rhinologic complaints undergoing CT imaging were recruited at an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 26 publications
(35 reference statements)
0
38
0
Order By: Relevance
“…Similarly, Likness et al compared multiple visual CT scoring systems with volumetric scoring based on manual CT segmentation and found that volumetric analysis was more sensitive to therapeutic effect 2 . Separately, Garneau et al 31 and Lim et al 3 each showed correlation between volumetric opacification scores and symptoms assessed using the Total Nasal Symptoms score and the 22‐item Sino‐Nasal Outcome Test. Although the results are promising, all of these efforts relied on manual or semiautomatic segmentation of the sinus cavities, which can take anywhere from 20 minutes 32 to several hours 33 to accomplish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Likness et al compared multiple visual CT scoring systems with volumetric scoring based on manual CT segmentation and found that volumetric analysis was more sensitive to therapeutic effect 2 . Separately, Garneau et al 31 and Lim et al 3 each showed correlation between volumetric opacification scores and symptoms assessed using the Total Nasal Symptoms score and the 22‐item Sino‐Nasal Outcome Test. Although the results are promising, all of these efforts relied on manual or semiautomatic segmentation of the sinus cavities, which can take anywhere from 20 minutes 32 to several hours 33 to accomplish.…”
Section: Discussionmentioning
confidence: 99%
“…There is a recognized unmet need for precise, objective evaluation of disease severity, and treatment response in chronic rhinosinusitis (CRS) 1‐3 . Computed tomography (CT) is the preferred modality for noninvasive imaging of the paranasal sinuses and plays a key role in evaluating CRS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the literature regarding correlation of these CT scoring systems and patient-reported outcomes has been mixed 8 . Interestingly, more recent studies using semi-automated volumetric analysis of CT scans have shown a higher degree of association with symptoms 9,10 , suggesting that more comprehensive methods of CT image analysis may be important for linking symptoms with objective measures of inflammation. These methods, however, are time-consuming and may not be practical for routine clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, a CNN is a biologically-inspired computer algorithm that uses thousands of simple units, modeled after neurons, that take an input from one layer of units, perform a mathematical transformation, and feed the output to the next set of neurons. Similar to their biological counterparts, while each individual neuron is simple to understand, structured networks of them have demonstrated complicated, emergent properties that are useful for pattern-recognition tasks 9,10 . These algorithms have been used to great effect in multiple applications 11 , most notably the ImageNet challenge, an annual international computer vision competition that asks computer scientists to develop algorithms to classify a given set of images into over 1,000 categories.…”
Section: Introductionmentioning
confidence: 99%